2010
DOI: 10.1590/s0102-311x2010000400018
|View full text |Cite
|
Sign up to set email alerts
|

Como a posição social influencia a auto-avaliação do estado de saúde? Uma análise comparativa entre 1998 e 2003

Abstract: Introdução É notória a relação entre medidas de saúde e variáveis sócio-econômicas, estudada segundo diferentes abordagens teóricas. Do ponto de vista econômico, por exemplo, isso se deve à importância da saúde como um determinante fundamental da capacidade produtiva das pessoas 1,2 . Ter boa saúde significa estar mais disposto a exercer atividades dentro e fora do mercado de trabalho. No campo sociológico, os estudos focam a interação entre condições de saúde e fatores socioculturais e biossociais, como statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
1
10
0
6
Order By: Relevance
“…In the present case, we have seen a positive precedence over self-perceived health (290, 57.9%) in young adults in relation to a negative perception (211, 42.1%), which was predominant in males, in school young adults who reported living in slums, in those who have an excellent or very good lifestyle and young adults who do not have or do not know if they have cases of stroke in their families. Many studies have shown that self-perceived health is useful to complement diagnosis and show adherence to certain health treatments, since certain sensations of the patient are not captured in the usual tests (12)(13) .…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, we have seen a positive precedence over self-perceived health (290, 57.9%) in young adults in relation to a negative perception (211, 42.1%), which was predominant in males, in school young adults who reported living in slums, in those who have an excellent or very good lifestyle and young adults who do not have or do not know if they have cases of stroke in their families. Many studies have shown that self-perceived health is useful to complement diagnosis and show adherence to certain health treatments, since certain sensations of the patient are not captured in the usual tests (12)(13) .…”
Section: Discussionmentioning
confidence: 99%
“…Entre esses grupos, destacam-se as diferenças observadas entre as atividades agrícolas e não agrícolas, as quais estariam associadas não somente à demanda física e estresse das atividades, mas também aos diferentes estilos e hábitos de vida saudável dos trabalhadores do campo e da cidade (RODRIGUES & MAIA, 2010). Em 2008, o mercado de trabalho brasileiro ainda apresentava um expressivo contingente de ocupados agrícolas (15,9 milhões de pessoas ou 18% dos ocupados), entre os quais a prevalência de saudáveis era 14 pontos percentuais inferior àquela observada no setor não agrícola (66% e 80%, respectivamente).…”
Section: Diferenças Entre Setoresunclassified
“…No entanto, apesar da conhecida relação positiva entre renda e estado de saúde, a baixa elasticidade da renda sobre a saúde, mesmo entre os ocupados não agrícolas, sugere que a renda não pode ser considerada como o fator delimitador do estado de saúde dos indivíduos. Existem outras condições, associadas à posição social dos ocupados, tais como diferenças culturais, exposição a diferentes riscos no ambiente de trabalho, acesso a serviços de saúde e expectativas diversas sobre o próprio estado de saúde entre ocupados de um mesmo setor, as quais a renda não consegue captar (RODRIGUES & MAIA, 2010).…”
Section: Diferenças Intrassetoriaisunclassified
“…The associations between health status and socioeconomic variables such as education and income, or demographics such as age and sex is well known 7,8,9,10 . However, less common are studies that attempt to examine other aspects of well-being that can be related to self-reported health status, such as the degree of happiness, the feeling of discrimination, satisfaction with the neighborhood, the adequacy of income to meet the needs and expectations of family spending.…”
Section: Introductionmentioning
confidence: 99%